Annexin V–CLIO: A Nanoparticle for Detecting Apoptosis by MRI - Eyk A. Schellenberger; Alexei Bogdanov; Dagmar Högemann; Jonathan Tait; Ralph Weissleder; Lee Josephson (Molecular Imaging)
Annexin V, which recognizes the phosphatidylserine of apoptotic cells, was conjugated to crosslinked iron oxide (CLIO) nanoparticles, a functionalized superparamagnetic preparation developed for target-specific magnetic resonance imaging (MRI). The resulting nanoparticle had an average of 2.7 annexin V proteins linked per CLIO nanoparticle through disulfide bonds. Using camptothecin to induce apoptosis, a mixture of Jurkat T cells (69% healthy and 31% apoptotic) was incubated with annexin V–CLIO and was applied to magnetic columns. The result was an almost complete removal of the apoptotic cells (>99%). In a phantom MRI experiment, untreated control cells (12% apoptotic cells, 88% healthy cells) and camptothecin-treated cells (65% apoptotic cells, 35% healthy cells) were incubated with either annexin V–CLIO (1.0, 0.5, and 0.1 μg Fe/mL) or with unlabeled CLIO. A significant signal decrease of camptothecin-treated cells relative to untreated cells was observed even at the lowest concentration tested. Unmodified CLIO failed to cause a significant signal change of apoptotic cells. Hence, annexin V–CLIO allowed the identification of cell suspensions containing apoptotic cells by MRI even at very low concentrations of magnetic substrate. Conjugation of annexin V to CLIO affords a strategy for the development of a MRI imaging probe for detecting apoptosis.